Contenidos de programación televisiva y su incidencia en los problemas de conducta de los adolescentes de la Parroquia Venus del Rio Quevedo - Macias Montes, Mercedes Isabel (2019)
A television channel is a source that allows people to relate as it becomes a physical materialization of the need to communicate and report different events among the members of a society. In a television medium, actions such as investigating, informing and disseminating social facts and problems must be carried out day by day. This is what keeps human beings informed and updated of everything that happens in their community and in the rest of the world. The national programming in recent years has shown transcendental changes in its entertainment spaces, its objectives are focused on selling more having a higher rating against the competition regardless of the cost that it has, the contents of national programming. In the local channels a series of soap operas presented at prime time can be observed at present, easy to be seen by a minor public, but without assessing some messages that are harmful, Ecuadorian television is innovating its contents and currently You can observe a large number of programs, series, soap operas with an understandable social content for all strata and that present realities with which the mental health audience of this human group can be identified. The national television channels have focused on betting on a more sensationalist, yellowish television where the misrepresentation of communication is seen as something everyday, behind are the good programs with values that highlighted the love of the family, currently betting on television programs with formats of other international realities where sex, violence is the first thing that is visualized and what is bet.